2014
DOI: 10.1007/s00382-014-2315-1
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the upper-ocean warm layer improves the simulation of the Madden–Julian oscillation

Abstract: 13Here we show that coupling a high-resolution one-column ocean model to an 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
95
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(118 citation statements)
references
References 59 publications
23
95
0
Order By: Relevance
“…Furthermore, the rainfall in the future experiment becomes larger, and the sea level pressure (SLP) shows a more strongly meridionally confined and intensified Kelvin wave-like perturbation to the east of the deep convection (Figures 3e and 3f); this causes stronger low-level moisture convergence (not shown) consistent with the frictional wave-conditional instability of the second kind (CISK) mechanism [Wang and Rui, 1990;Kang et al, 2013]. Because the intraseasonal moisture convergence À (∇ Á qV)′ is dominated by the MJO-scale convergence of the mean moisture, Àq (∇ Á V′) [Hsu and Li, 2012;Tseng et al, 2014], the changes in Δqδ ′ CTL at each composite phase of the MJO cycle is diagnosed instead. [Tseng et al, 2014] suggest that coupling leads to warmer SST and more moisture ahead of the deep convection.…”
Section: 1002/2015gl065095mentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the rainfall in the future experiment becomes larger, and the sea level pressure (SLP) shows a more strongly meridionally confined and intensified Kelvin wave-like perturbation to the east of the deep convection (Figures 3e and 3f); this causes stronger low-level moisture convergence (not shown) consistent with the frictional wave-conditional instability of the second kind (CISK) mechanism [Wang and Rui, 1990;Kang et al, 2013]. Because the intraseasonal moisture convergence À (∇ Á qV)′ is dominated by the MJO-scale convergence of the mean moisture, Àq (∇ Á V′) [Hsu and Li, 2012;Tseng et al, 2014], the changes in Δqδ ′ CTL at each composite phase of the MJO cycle is diagnosed instead. [Tseng et al, 2014] suggest that coupling leads to warmer SST and more moisture ahead of the deep convection.…”
Section: 1002/2015gl065095mentioning
confidence: 94%
“…The stronger convection is associated with much enhanced low-level moisture convergence (green contour in Figures 3a and 3b). [Tseng et al, 2014] suggest that coupling leads to warmer SST and more moisture ahead of the deep convection. By contrast, the meridionally overturning circulation is contracted meridionally toward an enhanced heating over 5°S (Figures 3c and 3d).…”
Section: 1002/2015gl065095mentioning
confidence: 99%
“…In particular, well‐resolved air‐sea interactions—subdaily (typically 3 hr) air‐sea exchanges and a fine (typically 1 m) oceanic vertical resolution—are required to capture the intraseasonal thermodynamic oceanic response to atmospheric forcing. Coarser spatial or temporal resolutions fail to simulate the peak diurnal SST warming and mixed‐layer shoaling during the MJO suppressed phase, which rectifies onto intraseasonal scales (e.g., Bernie et al, , ; Klingaman et al, ; Tseng et al, ). While the oceanic dynamical response to MJO forcing may be important for the development of subsequent MJO events that have no obvious atmospheric precursors (Webber et al, , ), GCM experiments (e.g., Klingaman & Woolnough, ; Tseng et al, ) and observational analysis (Halkides et al, ; Lau & Sui, ) show that most intraseasonal tropical SST variability can be recovered through thermodynamic air‐sea interactions alone, particularly for regions more than ±3° latitude from the equator.…”
Section: Introductionmentioning
confidence: 99%
“…As recent studies have shown, including a diurnal cycle is important to lower frequency physical processes (Clayson and Weitlich, 2007;Woolnough et al, 2007;Seo et al, 2014;Tseng et al, 2014).…”
Section: Modeling the Ocean Boundary Layermentioning
confidence: 99%